Mendelian genetics (Henry Stewart Talks, 2026)
Mendel's experiments, Principles of dominance and segregation, Genotype and phenotype concepts, Punnett squares for inheritance, Mendel\u2019s Laws of Segregation and Independent Assortment, Mendelian genetics in human traits, Mendelian principles in modern genetics